Algeria : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Informational Annex highlights that data provision in Algeria has some shortcomings, but is broadly adequate for surveillance. Data are published with a delay of less than one month. Key shortcomings in government finance statistics include insufficient institutional coverage, classification problems, long lags for production of statistics, and lack of reconciliation of financing with the monetary accounts. Key factors behind these weaknesses include the lack of financial resources allocated to the compilation of statistics, insufficient interagency coordination, and concern about accuracy that give rise to reluctance to publish provisional data. Monetary statistics compiled by the authorities are largely in line with the methodology in the 2000 Monetary and Financial Statistics Manual and its companion 2008Compilation Guide.